Determinants of Capital Expenditure in Indonesia: A Comprehensive Review of Economic, and Institutional Factors - Novi Sahillawardi; Abdul Manan; Endang Astuti (Future Techno-Science, 2025)
Capital investment or capital expenditure plays a vital role in supporting economic growth, especially in developing countries such as Indonesia. Capital expenditure includes spending on fixed assets, such as infrastructure, production facilities, and technology, which are the foundation for long-term sustainable development. In the Indonesian context, the priority of capital expenditure is directed towards accelerating infrastructure development, reducing inequality between regions, and increasing global competitiveness. However, challenges in optimizing this expenditure arise due to the lack of comprehensive understanding of the factors that influence it. At the local level, the relationship between the community as the principal and the government as the agent in resource management is crucial. The sub-district government has a strategic role in public services, infrastructure maintenance, and absorption of community aspirations. To increase public trust, responsible, transparent, and accountable management is needed. Collaboration between the community and the sub-district government is expected to encourage shared prosperity, with steps such as routine reporting, community empowerment, increasing the competence of the apparatus, and utilizing information technology. This literature highlights the importance of capital investment and resource governance at the local level as fundamental elements in strengthening inclusive and sustainable economic development.